'Answer in any way you want': Discursive tensions in conversations of a citizen participation process. (December 2021) - Sjögren, Maria
This paper contributes to empirical knowledge of citizen participation as a communicative event, by analyzing discursive tensions in interviews between civil servants and citizen-parents, that are part of a participatory process on how to mitigate violence in a suburban area in Sweden. Citizen participation events are increasingly initiated by public institutions in Western societies. Research, however, shows that goals of participatory processes often conflict with formal decision-making structures and institutional boundaries. Yet, how such tensions play out on the level of interaction is little researched. This study therefore analyzes discursive practices deployed by civil servants and how these construct characteristic tensions for the interviews. Three practices are identified: (1) pursuing the initial question, (2) cueing an institutional frame, and (3) epistemic positioning of the parents . These practices, being guided by an institutional agenda, create tensions both to the parents' lifeworld and for the ideals of the participatory method itself.